Implementation of Prototyping and System Usability Scale In The Point of Sales Information System at CV Kharisma Lestari - Antonius Antonius; Tony Darmanto; Thommy Willay (International Journal of Multidisciplinary Sciences and Arts, 2025)
CV Kharisma Lestari is a retail business that faces obstacles in its sales and inventory management systems due to its continued use of manual processes. This study aims to develop a Point of Sales (POS) Information System by applying the prototyping method to improve the operational efficiency of CV Kharisma Lestari. The prototyping method was chosen for its ability to actively involve users from the early stages, so that the resulting system can meet their needs and expectations. This study uses a Research and Development (R&D) approach with prototyping stages : communication, quick plan, modeling quick design, construction of prototype, and deployment delivery and feedback. The results of the study show that the POS system developed successfully automates the sales transaction process, manages inventory data in real-time, and generates accurate inventory and sales reports. The implementation of this system has a significant impact on reducing transaction time by up to 70% and increasing inventory data accuracy. The System Usability Scale (SUS) test on the system resulted in a score of 85.8, which indicates a very high level of user acceptance (usability). Thus, the prototyping method has proven to be effective in producing an information system that is not only functional but also easy to use, as it is able to capture user needs and feedback.